Regional Digital Business Platform - N. A. Dubko (Цифровая трансформация, 2020)
The article considers the importance of entrepreneurship development both for the region and for the country as a whole. The relevance of digitalization in Belarus is described. Some results of a questionnaire survey conducted with the participation of the author of small and medium-sized businesses of the Vitebsk region to study problems and necessary directions of regional entrepreneurship development were analyzed, carried out within the framework of the international technical assistance project. The necessity and prerequisites of creating a digital platform within which the management bodies interact with entrepreneurs are justified. The main goals of digital business platform creation, its ecosystem and main functions are presented, the conclusion on expediency of business platform functioning is made.